1997
DOI: 10.1126/science.277.5333.1808
|View full text |Cite
|
Sign up to set email alerts
|

Cichlid Fish Diversity Threatened by Eutrophication That Curbs Sexual Selection

Abstract: Cichlid fish species of Lake Victoria can interbreed without loss of fertility but are sexually isolated by mate choice. Mate choice is determined on the basis of coloration, and strong assortative mating can quickly lead to sexual isolation of color morphs. Dull fish coloration, few color morphs, and low species diversity are found in areas that have become turbid as a result of recent eutrophication. By constraining color vision, turbidity interferes with mate choice, relaxes sexual selection, and blocks the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
1,124
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,105 publications
(1,153 citation statements)
references
References 33 publications
25
1,124
4
Order By: Relevance
“…Despite over half a century of work conducted on the Trinidadian guppy in both predator-prey and sexual selection research (reviewed in Houde 1997;Magurran 2005), however, we are uncertain exactly how increasing turbidity affects such ecological interactions. Increasing turbidity may affect the ability of some aquatic species to assess mates (Seehausen 1997;Engström-Öst and Candolin 2007), or maintain sufficient foraging rates (Gardner 1981). Increased activity required to forage or find mates may thus affect the trade-off between foraging and/or courting and avoiding predation (Sih 1992).…”
Section: Further Study and Concluding Remarksmentioning
confidence: 99%
“…Despite over half a century of work conducted on the Trinidadian guppy in both predator-prey and sexual selection research (reviewed in Houde 1997;Magurran 2005), however, we are uncertain exactly how increasing turbidity affects such ecological interactions. Increasing turbidity may affect the ability of some aquatic species to assess mates (Seehausen 1997;Engström-Öst and Candolin 2007), or maintain sufficient foraging rates (Gardner 1981). Increased activity required to forage or find mates may thus affect the trade-off between foraging and/or courting and avoiding predation (Sih 1992).…”
Section: Further Study and Concluding Remarksmentioning
confidence: 99%
“…Sexual selection is the other major factor that is likely to have contributed to the cichlids' species-richness (see, e.g., Meyer 1993;Salzburger 2009;Seehausen et al 1997;Turner & Burrows 1995), as indicated by the occurrence of multiple color morphs and sexual color dimorphism. This is particularly obvious in the most species-rich group of cichlids, the haplochromines.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies provide tantalizing evidence that sexual selection may cause speciation in the wild (Coyne & Orr 1989Barraclough et al 1995;Seehausen et al 1997;Gray & Cade 2000;Masta & Maddison 2002), yet support for this hypothesis remains incomplete. To demonstrate conclusively that sexual selection drives speciation, several criteria must be met: male signals must differ significantly among populations or recent sister species; females must prefer local male signals to foreign ones; divergence in male signals must result from selection and not genetic drift; and finally, divergent signals and preferences must be correlated with restricted gene flow at nuclear loci to show that populations are diverging towards distinct species (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Coyne & Orr 1989Seehausen et al 1997;Masta & Maddison 2002), and some have also demonstrated female preferences for local male signals (e.g. Seehausen et al 1997;Gray & Cade 2000).…”
Section: Introductionmentioning
confidence: 99%